Delayed diagnosis of complex glycerol kinase deficiency in a Chinese male infant: a case report - Na Tao; Xiaomei Liu; Yueqi Chen; Meiyuan Sun; Fang Xu; Yanfang Su (BMC, 2022)
Abstract Background Xp21 contiguous gene deletion syndrome is a rare genetic metabolic disorder with poor prognosis in infants, involving deletions of one or more genes in Xp21. When deletions of adrenal hypoplasia (AHC), Duchenne muscular dystrophy (DMD), and chronic granulomatosis (CGD) loci are included, complex glycerol kinase deficiency (CGKD) can be diagnosed. We present a case of CGKD that was initially misdiagnosed and died during treatment in our hospital in terms of improving our understanding of the clinical features and diagnosis of this disease, as well as highlighting the need for more precise dosing of corticosteroid replacement therapy. Case presentation A 48-day-old full-term male infant was transferred to our medical center with global growth delay and persistent vomiting. Routine laboratory tests revealed hyperkalemia, hyponatremia, and a high level of creatine kinase. The initial diagnosis was adrenal cortical hyperplasia (ACH), then revised to adrenocortical insufficiency with a normal level of ACTH detected. After supplementing the routine lipid test and urinary glycerol test, CGKD was diagnosed clinically due to positive triglyceridemia and urinary glycerol, and the follow-up gene screening further confirmed the diagnosis. The boy kept thriving after corticosteroid replacement and salt supplementation. While levels of serum ACTH and cortisol decreased and remained low after corticosteroid replacement was administered. The patient died of acute type 2 respiratory failure and hypoglycemia after an acute upper respiratory tract infection, which may be the result of adrenal crisis after infection. Infants with CGKD have a poor prognosis, so physicians should administer regular follow-ups, and parents counseling during treatment to improve the survival of patients. Conclusions Overall, CGKD, although rare, cannot be easily excluded in children with persistent vomiting. Extensive blood tests can help to detect abnormal indicators. Adrenal crisis needs to be avoided as much as possible during corticosteroid replacement therapy.